AUGMENTATIVE COMMUNICATION SYSTEMS: HUMAN DEVELOPMENT AS A METAPHOR FOR COMPUTER DEVELOPMENT - PART II - Desson, Jim (McGill Journal of Education / Revue des sciences de l'éducation de McGill, 1985)
A model of the developmental interdependence of the individual and collective mankind is used as a metaphor for the development of the computer and telecommunications. This model of computer development, which incorporates models of metaphor and Gordon Thompson's "shared space" concept of communication, is used to evaluate the development of computer-aided augmentative communication systems - past, present, and future - which are used by non-vocal severely physically handicapped people. RÉSUMÉ Un modèle de l'inter-dépendance développementale de l'humanité individuelle et collective sert de métaphore à l'évolution de l'informatique et des télécommunications. Ce modèle de développement informatique qui comporte des modèles de métaphore ainsi que le concept de communication en "espace partagé" de Gordon Thompson, sert à évaluer la mise au point de systèmes de communication additifs assistés par ordinateur (passés, présents, et futurs) qui sont utilisés par les handicapés physiques muets.